An Empirical Investigation of IPO Underpricing in Chinese A-share Market (2003-2012) - Liu, Ying (2013)
China has the extreme high level of IPO underpricing in comparison to other developed stock markets. This dissertation investigates the driving factors of Chinese IPO underpricing degree by using a data sample of 963 A-share IPOs listed on Shanghai Stock Exchange and Shenzhen Stock Exchange during year 2003 to 2012. The empirical results of this dissertation suggest that winner’s curse theory, ex-uncertainty theory and underwriter reputation hypothesis are not applicable in Chinese stock market based on the sample data. As a matter of fact, inequity of demand and supply acts as the main explanation of Chinese IPO underpricing, while agency cost theory, time interval hypothesis and information cascades effect hypothesis have very high explanatory power, despite that the test result of signalling theory is opposite to the expectation. This study also figures out that the equity separation reform and the change of pricing mechanism during the sample period even aggravate Chinese IPO underpricing to some degree. It is concluded that IPO underpricing level has decreased gradually because of the development of Chinese stock market. Finally, limitation of this study and some suggestions for further research are indicated.